L’évolution du « modèle » de Brasilia : vers une métropole banale ? - Hervé Théry (Cahiers des Amériques Latines)
The "window" which should have been Brasilia is menaced, notably by the explosive urban expansion which the town is experiencing. This questions the model desired by its conceivers who wanted to create a “green” town, but also something logic and fluid, and a model of fraternity between its inhabitants, rich and poor. Forty years after its foundation, the town counts more than 2 million inhabitants and is marked by strong social disparities which the recent publication of the data of 2000’s demographic census permits us to analyse in detail.